STUDI EVALUASI DAN PERENCANAAN SISTEM JARINGAN DRAINASE PADA BAGIAN WILAYAH KOTA ( BWK II ) UNAAHA KABUPATEN KONAWE SULAWESI TENGGARA - Irvan Umar (Media Teknik Sipil, 2011)
City Area II ( BWK II ) Unaaha since 1982 became the capital of Kendari Residence anddeveloped into Konawe residence in 2004 as the shape of regional autonomy spirit and developmentin northeast Sulawesi.Drainage Sistem condition in Unaaha city could be said lack ability in supportingbanishment whether from household waste or rain debt as hydrology effect happened in the area. Itmade Unaaha faced serious matters caused by flood which happened in several regions, especiallywhen rainy season came. So, there needed evaluation of canal capacity and new drainage systemplanning.According to evaluation, there found that there were several canal which didn’t able to interceptflood debt in 2 years ( Q 2 years ), so that needed re-plan of canal plane. New drainage canalplanning also needed to reduce water slick when it rained. There also needed supporting buildings,water channels in drainage which able to minimize the slick area.Key word : Drainage, flood debt, normalization, planning evaluation